THE AFFECT OF PRICE AND TRUST TOWARD BRAND SWITCHING OF SMARTPHONE IN MANADO - Tumbol, Indah Permata; Lapian, Joyce .; Worang, Frederik G (Universitas Sam Ratulangi, 2017)
Abstract: The smartphone revolution has triumphed in Indonesia especially in Manado in terms of penetration and innovation. Therefore, as the competition becomes more intensified, it is important to any companies to anticipate any changes in its customersâ€™ preferences, especially all variables related to the price and trust that are much revealed in prior studies. This study is to know the affect of price and trust on brand switching. Switching behaviour of subscribers has many factors behind it, but in this case we just need to analyze two factors which is price and trust. By using 100 respondents, we used multiple regression to analyze the data. The results reveal that price and trust are significantly positive related to brand switching. Based on the result, the author suggest for smartphone companies to be careful about the safety product by consistently give right products without defect and to maintain price in order to meet customer expectation. Consistent price that compatible with the product usability increase customer satisfaction and encourage repeat purchases.Â Keywords: price, trust, brand switchingÂ